Discrete fractional calculus with exponential memory: Propositions, numerical schemes and asymptotic stability - Yang, Guang; Wu, Guo-Cheng; Fu, Hui (Nonlinear Analysis: Modelling and Control, 2023)
A new fractional difference with an exponential kernel function is proposed in this study. First, a difference operator is defined by the exponential function. From the Cauchy problem of the nth-order difference equation, new fractional-order sum and differences are presented. The propositions between each other and numerical schemes are derived. Finally, fractional linear difference equations are presented, and exact solutions are given by using a new discrete Mittag-Leffler function.